Development and Evaluation of a Caregiver Reported Quality of Life Assessment Instrument in Dogs With Intracranial Disease - Weiske, Rebecca; Sroufe, Maureen; Quigley, Mindy; Pancotto, Theresa; Werre, Stephen; Rossmeisl, John H. (Frontiers in Veterinary Science, 2020)
In veterinary medicine, quality of life (QOL) assessment instruments, which are important components of the holistic evaluation of treatment success, have largely not included organ-specific concerns that may be broadly relevant to caregivers of dogs with intracranial disease. The objective of this study was to identify core questionnaire items and domains that contribute to health-related QOL (HRQOL) in dogs with intracranial disease. A questionnaire was developed that contained 39 QOL-related items encompassing physical, social/companionship, and brain-specific domains associated with the treatment of dogs with intracranial disease, and administered to caregivers of 56 dogs diagnosed with genetic, inflammatory, neoplastic, traumatic, and vascular brain diseases, 52 healthy dogs, and 20 dogs with non-neurological illnesses. Clinician derived functional measures of each dog’s health status including chronic pain, Karnofsky performance, and modified Glasgow coma scale scores were also recorded. Principal component analysis refined the final questionnaire, termed the CanBrainQOL-24, to 24-items within the three domains with a minimum Cronbach’s alpha of 0.7, indicative of good internal consistency. The CanBrainQOL-24 discriminated between healthy and diseased dogs. Physical and brain-specific domains were significantly different between dogs with intracranial and non-neurological diseases. Significant correlations were observed between owner reported visual analog scores and CanBrainQOL-24 scores, as well between clinician derived functional status measures and owner reported QOL. The CanBrainQOL-24 contains core questions relevant to caregiver assessment of HRQOL in dogs with a variety of intracranial diseases, and provides information that is complementary to clinician derived functional outcome measures.